Oxygen transfer investigations in an aerobic granular sludge reactor. Issue 3 (3rd January 2020) - Cecconi, Francesca; Garrido-Baserba, Manel; Eschborn, Ralph; Damerel, Jordan; Rosso, Diego
Abstract : Oxygen transfer efficiency during the aeration cycle for all the experiments. Abstract : The aerobic granular sludge process is an alternative to the conventional activated sludge process adopted in water resource recovery facilities. This study presents the first independent assessment of aerobic granular sludge technology in terms of oxygen transfer efficiency and nutrient removal performance. Using off-gas testing, a full-depth pilot reactor with granular biomass was compared to an identical reactor with floccular biomass. The granular process presented lower oxygen transfer efficiency than the floccular sludge (2.3%/m vs. 3.2%/m, respectively). The granular sludge was also tested at different operating conditions in order to address potential retrofitting for existing aeration basins. With regard to oxygen transfer efficiency, the experiments show a marginal improvement at lower MLSS (∼0.2%/m) and at medium side-water-depth (∼0.3%/m). Satisfactory effluent water quality levels, in terms of nitrogen and phosphorous removal, were obtained for the granular sludge except for decreased MLSS conditions during which the nitrification/denitrification process was highly penalized.